2015
DOI: 10.1105/tpc.115.136234
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4-Phosphate Negatively Regulates Chloroplast Division in Arabidopsis

Abstract: Chloroplast division is performed by the constriction of envelope membranes at the division site. Although constriction of a ring-like protein complex has been shown to be involved in chloroplast division, it remains unknown how membrane lipids participate in the process. Here, we show that phosphoinositides with unknown function in envelope membranes are involved in the regulation of chloroplast division in Arabidopsis thaliana. PLASTID DIVISION1 (PDV1) and PDV2 proteins interacted specifically with phosphati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 54 publications
2
19
0
2
Order By: Relevance
“…These findings suggest that increased levels of membrane PI4P and PI(4,5)P 2 could also disrupt thylakoid formation and grana assembly during chloroplast development in rice. Interestingly, this result coincides with reported evidence whereby inhibition of PI4P synthesis accelerates chloroplast division, supporting the idea that PI4P negatively regulates chloroplast division in Arabidopsis (Okazaki et al, 2015). Taken together, these findings suggest that the massive accumulation of membrane PI4P and PI(4,5)P 2 resulting from terminated GH1 production could disturb organelle development and cytoarchitecture.…”
Section: Resultssupporting
confidence: 90%
“…These findings suggest that increased levels of membrane PI4P and PI(4,5)P 2 could also disrupt thylakoid formation and grana assembly during chloroplast development in rice. Interestingly, this result coincides with reported evidence whereby inhibition of PI4P synthesis accelerates chloroplast division, supporting the idea that PI4P negatively regulates chloroplast division in Arabidopsis (Okazaki et al, 2015). Taken together, these findings suggest that the massive accumulation of membrane PI4P and PI(4,5)P 2 resulting from terminated GH1 production could disturb organelle development and cytoarchitecture.…”
Section: Resultssupporting
confidence: 90%
“…Only one study has detected PIP by radiolabeling experiments and found it, preferentially, in the outer leaflet of the chloroplast envelope (70). Mutants lacking enzymes for PI4P synthesis have more chloroplasts per cell, suggesting that PI4P negatively regulates chloroplast division (71). PI4P might also be a minor lipid in the chloroplast inner envelope membrane, where it could be bound by stromal proteins such as CPSFL1 and VIPP1 (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these and other results, the authors proposed that PDV1 interaction with PI4P in the chloroplast envelope alters PDV1 affinity for DRP5B, which may alter the rate of chloroplast division. These findings implicate phosphoinositide signaling in the regulation of chloroplast division (Okazaki et al, 2015).…”
Section: Regulation Of Chloroplast Divisionmentioning
confidence: 63%
“…Recently, Okazaki et al (2015) reported that the phosphoinositide phosphatidylinositol 4-phosphate (PI4P) negatively regulates chloroplast division in Arabidopsis. Inhibition of phosphatidylinositol 4-kinase to reduce PI4P levels in chloroplast membranes accelerated chloroplast division, producing a larger population of smaller chloroplasts, similar to overexpression of PDV proteins (Okazaki et al, 2009).…”
Section: Regulation Of Chloroplast Divisionmentioning
confidence: 99%